ACCESSIBILITY OF FINANCIAL INFORMATION IN RELATION TO CHANGES IN SIZE OF ENTITIES CAUSED BY THE COVID‐19 CRISIS - Małgorzata Garstka (Polityki Europejskie, Finanse i Marketing)
The consequences of the Covid-19 pandemic on the quality and scope of financial information prepared by accounting are complex. The scope of the financial statement and the obligation to audit depend on the classification of units based on their size. The required scope is narrower for micro and small entities than it is for larger organizations. The crisis may have influenced the size of entities and by that their classification and the scope of information that they need to disclose. The goal of this article is to verify whether post-pandemic demands for information, assuming it will be the same as pre-pandemic, can be fulfilled. The accessibility of information is connected with the level of security of engaging in business activities. Making changes in the criteria of an entity’s inclusion as an SME and in its obligation to audit can be one solution for the problem of insufficient information. The methodology used in this study is analysis of regulations and deductive reasoning. It showed that the effects of the pandemic, particularly the increase in the number of micro and small entities, can limit the accessibility of information. This article contributes to the scientific literature by displaying and justifying the need to verify the classification criteria of businesses and other entities.